The Scarring and Hysteresis Effects of Steep Recessions and the Implications for Fiscal Policy in ECA Transition EMDEs - Brownbridge, Martin (World Bank, Washington, DC, 2021)
The deep recession in many of the emerging market transition economies of Europe and Central Asia caused by the COVID-19 crisis has raised fears of long-term damage to potential output through scarring and hysteresis. These economies were also hit hard by the great recession caused by the global financial crisis. This paper provides empirical estimates of the impact of the great recession on the subsequent medium-term level of real gross domestic product in a sample of 65 middle-income countries. It finds evidence of a significant hysteresis parameter in these countries. The paper also examines how the combination of a hysteresis parameter and a positive fiscal multiplier can mean that a countercyclical fiscal expansion that successfully mitigates the output loss in a recession need not worsen public debt levels in the medium to long term because of its positive impact on potential output and thus the tax base.